THU0066 CR6086, a Selective Antagonist at the EP4 Prostanoid Receptor, Improves or Resolves Disease Features in a RAT Model of Rheumatoid Arthritis. (9th June 2015) - Chiusaroli, R.; Grotti, A.; Lanza, M.; Caselli, G.; Rovati, L.
Abstract : Background: Recent studies highlight the role of the EP4 prostanoid receptor in promoting autoimmune inflammation via T helper cells, Th1 and Th17. Objectives: Aim of the present studies was to test CR6086, an EP4 selective antagonist, in a widely recognized animal model for rheumatoid arthritis, i.e. the collagen II-induced arthritis (CIA) model in the Lewis rat. The effect of CR6086 was studied in comparison to the JAK kinase inhibitor DMARD tofacitinib. Methods: 60 Lewis male rats were immunized with collagen type II in CFA. Three weeks after the first immunization, the same animals were boosted with the same method. Three days after booster injection, edema was assessed and the animals were then randomized and assigned to the treatment groups (n=12): vehicle; tofacitinib 5 mg/kg b.i.d.; tofacitinib 25 mg/kg b.i.d.; CR6086 15 mg/kg o.a.d. Edema measurement was performed again after 7 and 14 days of treatment, and then hindlimb joints were blindly scored for clinical signs of arthritis (scale 0-4). Hindpaw joints were blindly scored for histological features: edema; synovial hyperplasia; inflammatory cell infiltrate; cartilage damage; bone erosion; periosteal osteogenesis (scale 0-4). Statistical analyses were performed with ANOVA followed by Dunn's or Holm-Sidak's tests comparing all treatment groups vs. vehicle. Results: After 7 days of treatment, edema was significantly reduced in all treatment groups compared to vehicle (vehicle: 2.16±0.09; CR6086 15 mg/kg o.a.d. 1.77±0.07, p<0.05 vs. control; tofacitinib 5 mg/kg b.i.d. 1.80±0.1, p<0.05 vs. control; tofacitinib 25 mg/kg b.i.d. 1.71±0.04, p<0.05 vs. control). After 14 days of treatment, all treatments completely abated the edema, as measured by paw swelling (vehicle: 2.15±0.05; CR6086 15 mg/kg o.a.d. 1.64±0.03, p<0.05 vs. control; tofacitinib 5 mg/kg b.i.d. 1.68±0.04, p<0.05 vs. control; tofacitinib 25 mg/kg b.i.d. 1.62±0.03, p<0.05 vs. control). Administration of tofacitinib was associated with a profound, dose-dependent decrease of the arthritis clinical score compared to vehicle. CR6086 15 mg/kg also demonstrated very potent activity in reducing severity of arthritis clinical score (vehicle: 3.80±0.12; CR6086 15 mg/kg o.a.d. 1.42±0.27, p<0.05 vs. control; tofacitinib 5 mg/kg b.i.d. 2.25±0.31, p<0.05 vs. control; tofacitinib 25 mg/kg b.i.d. 0.69±0.09, p<0.05 vs. control). All histological features of arthritis were profoundly and significantly ameliorated following treatment with CR6086; administration of tofacitinib 25 mg/kg b.i.d. showed similar efficacy to CR6086 15 mg/kg/die, while tofacitinib 5 mg/kg b.i.d. displayed a lesser effect (Fig. 1 ). Conclusions: In a widely recognized animal model for rheumatoid arthritis, both CR6086 and tofacitinib demonstrated very good efficacy in all parameters examined, including edema, clinical arthritis score, and histological features. The present data suggest that CR6086 may be superior to tofacitinib in terms of potency, in this model. CR6086 is now in clinical phase I. Disclosure of Interest: R. Chiusaroli Employee of: Rottapharm Biotech Srl, A. Grotti Employee of: Rottapharm Biotech Srl, M. Lanza Employee of: Rottapharm Biotech Srl, G. Caselli Employee of: Rottapharm Biotech Srl, L. Rovati Shareholder of: Rottapharm Biotech Srl, Employee of: Rottapharm Biotech Srl